Advanced Nonlinear Strategies for Vibration Mitigation and System Identification - Vakakis, Alexander F.; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
The papers in this volume address advanced nonlinear topics in the general areas of vibration mitigation and system identification, such as, methods of analysis of strongly nonlinear dyanmical systems; techniques and methodologies for interpreting complex, multi-frequency transitions in damped nonlinear responses; new approaches for passive vibration mitigation based on nonlinear targeted energy transfer (TET) and the associated concept of nonlinear energy sink (NES); and an overview and assessment of current nonlinear system identification techniques.
Mitigation Strategies for Systems Subjected to Vibratory, Shock and Seismic Loads -- Targeted Energy Transfer in Systems with Periodic Excitations -- Advanced Strategies for Nonlinear System Identification -- CISM Courses and Lectures: Resonant energy exchange in nonlinear oscillatory chains and Limiting Phase Trajectories: from small to large systems -- Signal Processing for Experiments with Nonlinear Energy Sinks -- Nonlinear Targeted Energy Transfer and its Application to Vibration Mitigation.
Keywords: Engineering; Vibration; Engineering; Vibration, Dynamical Systems, Control